2010
DOI: 10.3109/02688697.2010.487131
|View full text |Cite
|
Sign up to set email alerts
|

Neuralgia of the glossopharyngeal and vagal nerves: long-term outcome following surgical treatment and literature review

Abstract: This study describes our experience in the surgical treatment of neuralgia of the glossopharyngeal and vagal nerves. Over the last 19 years, 21 patients underwent surgery. Their case notes were reviewed to obtain demographic information, clinical presentation, surgical findings and early results. All patients were then contacted by telephone for long-term results and complications. Independent analysis of results was carried out by a Neurology team. Ten patients had microvascular decompression (MVD). Four pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 16 publications
1
54
0
5
Order By: Relevance
“…As a result, no sex effect could be identified [53]. With regard to vagoglossopharyngeal neuralgia, researchers reported that there was no preponderance regarding sex [54,55]. I gave a supplementary explanation for the term "vagoglossopharyngeal neuralgia".…”
Section: Vagus Nervementioning
confidence: 99%
“…As a result, no sex effect could be identified [53]. With regard to vagoglossopharyngeal neuralgia, researchers reported that there was no preponderance regarding sex [54,55]. I gave a supplementary explanation for the term "vagoglossopharyngeal neuralgia".…”
Section: Vagus Nervementioning
confidence: 99%
“…39 Since that time, this operation has gained greater acceptance than the traditional rhizotomy procedures and many series have been published regard ing its efficacy. [15][16][17]26,30,34,39,[45][46][47]50,56,60,67 Percutaneous procedures have been devised as an alternative to craniotomy; these procedures include ra diofrequency rhizotomy 2,4,12,18,21,40,55 and trigeminal trac totomy. 27,28,38 Most recently, stereotactic radiosurgery has also been explored.…”
Section: 41mentioning
confidence: 99%
“…20,22,27,28 It is also well demonstrated that the rate of pain control is slightly better with rhizotomy (95%) than with MVD (86%). In our series all the patients had satisfactory improvement except one patient who had persistent pain Other noninvasive treatment options have been described: Percutaneous radiofrequency neurolysis is an alternative in cases who failed medical treatment or in which they cannot undergo intracranial surgery.…”
Section: Discussionmentioning
confidence: 73%
“…[19][20][21] MVD series have reported good outcomes in 90-98%, long-term pain improvement have been observed in 64% with a low mortality ranging from 0% to 5.8%. 22 Currently, the MVD procedure is perceived as the most effective treatment for TN with the most satisfactory outcomes. The purpose of this study was to evaluate the anatomical variations in pathophysiology and role of MVD as a better treatment option in medically refractory cases in this series of cases of Trigeminal neuralgia.…”
Section: Introductionmentioning
confidence: 99%